Korupsi Pengelolaan Sumber Daya Alam Dalam Tinjauan Pasal 33 Ayat (3) Undang-Undang Dasar 1945 - Patty, Jetty Martje (MATAKAO Corruption Law Review, 2024)
Introduction: Cases of corruption still occur even in natural resource management even though the Constitution of the Republic of Indonesia in article 33 paragraph (3) has mandated that the earth, water and natural resources are controlled by the state and intended for the prosperity of the people. Purposes of the Research: The legal issue raised is how corruption in natural resource management is reviewed from article 33 paragraph (3) of the 2945 Constitution. Methods of the Research: This research is a normative research with a statutory approach that regulates corruption combined with a conceptual approach. Results of the Research: The result of this study is that corruption that occurs in the natural resource management sector shows that the State (unscrupulous government officials) is inconsistent in carrying out the mandate of article 33 paragraph (3) of the 1945 Constitution, the power given is used as a means for personal / individual interests by committing corruption. Abuse of power or authority leads to corruption.